School intervention to improve mental health of students in Santiago, Chile: a randomized clinical trial - Araya, Ricardo; Fritsch, Rosemarie; Spears, Melissa; Rojas, Graciela; Martinez, Vania; Barroilhet, Sergio; Vöhringer, Paul; Gunnell, David; Stallard, Paul; Guajardo, Viviana; Gaete, Jorge; Noble, Sian; et al. (JAMA pediatrics, 2013)
Depression can have devastating effects unless prevented or treated early and effectively. Schools offer an excellent opportunity to intervene with adolescents presenting emotional problems. There are very few universal school-based depression interventions conducted in low- and middle-income countries. To assess the effectiveness of a school-based, universal psychological intervention to reduce depressive symptoms among adolescents from low-income families. A 2-arm, parallel, cluster, randomized clinical trial was conducted in secondary schools in deprived socioeconomic areas of Santiago, Chile. Almost all students registered in the selected schools consented to take part in the study. A total of 2512 secondary school students from 22 schools and 66 classes participated. Students in the intervention arm attended 11 one-hour weekly and 2 booster classroom sessions of an intervention based on cognitive-behavioral models. The intervention was delivered by trained nonspecialists. Schools in the control arm received the standard school curriculum. Scores on the self-administered Beck Depression Inventory-II at 3 months (primary) and 12 months (secondary) after completing the intervention. There were 1291 participants in the control arm and 1221 in the intervention arm. Primary outcome data were available for 82.1% of the participants. There was no evidence of any clinically important difference in mean depression scores between the groups (adjusted difference in mean, -0.19; 95% CI, -1.22 to 0.84) or for any of the other outcomes 3 months after completion of the intervention. No significant differences were found in any of the outcomes at 12 months. A well-designed and implemented school-based intervention did not reduce depressive symptoms among socioeconomically deprived adolescents in Santiago, Chile. There is growing evidence that universal school interventions may not be sufficiently effective to reduce or prevent depressive symptoms. isrctn.org Identifier: ISRCTN19466209.